Mechanochemical synthesis of mononuclear gold(i) halide complexes of diphosphine ligands with tuneable luminescent properties. Issue 38 (1st September 2021) - Deák, Andrea; Jobbágy, Csaba; Demeter, Attila; Čelko, Ladislav; Cihlář, Jaroslav; Szabó, Pál T.; Ábrányi-Balogh, Péter; Crawford, Deborah E.; Virieux, David; Colacino, Evelina
Abstract : A mechanochemical method was developed for the synthesis of Au(XantPhos)X (1 : X = Cl; 2 : X = I) and Au( N -XantPhos)Cl (3 ) complexes. Abstract : A mechanochemical method is reported for the synthesis of Au(diphos)X complexes of diphosphine (diphos = XantPhos and N -XantPhos) ligands and halide ions (X = Cl and I). The Au(XantPhos)X (1 : X = Cl; 2 : X = I) and Au( N -XantPhos)Cl (3 ) complexes exhibited either yellowish green (1 ) or bluish green (2 ) emission, whereas 3 was seemingly non-emissive in the solid state at room temperature. Blue- (2B ) and bluish green (2G ) luminescent concomitant solvates of 2 were obtained by recrystallization. Luminescent colour changes from blue (2B ) or bluish green (2G ) to yellow were observed when these forms were subjected to mechanical stimulus, while the original emission colour can be recovered in the presence of solvent vapours. Moreover, the luminescence of 2B can be reversibly altered between blue and yellow by heating/cooling-cycles. These results demonstrate the power of mechanochemistry in the rapid (4 min reaction time), efficient (up to 98% yield) and greener synthesis of luminescent and stimuli-responsive gold(i ) complexes.